2017
DOI: 10.1155/2017/8147075
|View full text |Cite
|
Sign up to set email alerts
|

Can Limited Education of Lung Ultrasound Be Conducted to Medical Students Properly? A Pilot Study

Abstract: Objectives. Lung ultrasonography (LUS) is a useful examination to identify lung problems. Unfortunately, there are currently no LUS educational programs for medical students. We designed a brief LUS training course for medical students during the ED rotation. The purpose of training was improving cognitive and psychomotor learning domains, knowledge of ultrasound, knowledge of LUS, image acquisition, and image interpretation. Methods. Forty students in their fourth year of medical school were enrolled in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Only a few previous papers have shown a possible association between ultrasound-based seminars and performance at exams, even with several limitations. Lim et al (13) suggested that limited exposition of medical students to the ultrasound technique could improve their performances, and also Bell et al (3) reported similar results in cardiac physiology teaching. In our experience, all of the questions reviewed by the expert board were pertinent to the syllabus and to the UIL, and 90% of students said that they found the UIL pertinent to the syllabus.…”
Section: Discussionmentioning
confidence: 87%
“…Only a few previous papers have shown a possible association between ultrasound-based seminars and performance at exams, even with several limitations. Lim et al (13) suggested that limited exposition of medical students to the ultrasound technique could improve their performances, and also Bell et al (3) reported similar results in cardiac physiology teaching. In our experience, all of the questions reviewed by the expert board were pertinent to the syllabus and to the UIL, and 90% of students said that they found the UIL pertinent to the syllabus.…”
Section: Discussionmentioning
confidence: 87%
“…23,28,29 Automating the detection of canonical findings of LUS, these techniques are convenient and serve to achieve what clinicians may be trained to do with minimal training. 30 With attention to COVID-19, LUS has been shown to inform clinical course and outcome 31 , creating some further momentum toward broader LUS competence. As our work opens the door toward plausible early, automated COVID identification using LUS, DL techniques to auto-generate clinical severity score for COVID has also recently been described.…”
Section: Discussionmentioning
confidence: 99%
“…Beaulieu et al, an initial web-based theoretical program followed by hands-on training performed by simulation and on both healthy and sick individuals, improved the ability of 37 junior emergency medicine residents to recognize both venous vessels (5.5 h) and pleura (2.5 h) [13]. Lim et al showed that a 3-h educational course of lung ultrasound, combining 1 h of theory and 2 h of hands-on training on healthy subjects, significantly improved 40 medical students’ knowledge, image acquisition, and interpretation [14]. Melamed et al administered a 2-h theoretical instruction on transthoracic echocardiography followed by a 4-h hands’ training on critically ill patients with (20 patients) or without (24 patients) left ventricular abnormalities, to previously untrained ICU physicians [15].…”
Section: Discussionmentioning
confidence: 99%